LANGUAGE FUNCTION FOUND IN MIZONE FRES’IN TELEVISION COMMERCIAL - SUPRIYONO, ENDY RIZKY PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Language functions, Mizone Fres’in television commercial. Language is one of the most important parts of human life which deals with society as a tool that is used to communicate and transfer information to others. In society, people use language to create a communication system in order to reach the goal of the communication itself which is all about getting the message and understanding the meaning that depends on the context. From communication, language function can be created as well. The writer conducts a study about language functions that are found in Mizone Fres’in television commercial by using Hymes and Gumperz’s theory (1964). This study focuses on a problem: What language functions are found in Mizone Fres’in television commercial.This study uses qualitative approach in document analysis to analyze the language functions found in Mizone Fres’in television commercial. The data are the transcribed utterances produced by the two store keeper in Mizone Fres’in television commercials, Mizone Fres’in and Mizone Isotonic which are downloaded from Youtube website. This study discovers that eight components of communication are presented in Mizone Fres’in television commercial namely addresser, addressee, channel, code,setting, message-form, topic, and event. This study also discovers three out of eightfunctions of language. Those are directive function, phatic function, and referentialfunction. Referential function is the most frequently used function since the data wastaken from an advertisement that contained some information related to MizoneFres’in product. Basically, a company uses an advertisement as a tool to inform orshare product knowledge of certain brand to the people as the consumers in whichcertain purpose contained. The writer also finds that double function could exist.Double function is two or more functions that exist in an utterance. In brief, theexistence of language function depends on components of communication.Through this study, the future researchers are expected to investigate languagefunctions from other object beside document analysis. The writer suggests the nextresearchers apply other theories of language function from different experts. Thewriter also suggests the students of Study Program of English who are interested inconducting language function study learn more about functions that can exist in alanguage.